Approach for Complexity Management in Variant-rich Product Development - Wolfgang Vogel; Rainer Lasch (Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 22, 2015)
During the last years, companies in high-technology marketplaces were confronted with technology innovations, dynamic markets, changing customer requirements and uncertainty. Manufacturing companies can't escape these trends. To cope with these trends, companies try to develop new product variants, which lead to increased complexity. Product development is characterized by different factors such as product, product portfolio and the development process. Complexity management in product development is a strategic issue for companies to be competitive. A systematic literature review was performed to identify and analyze the existing approaches for complexity management in all fields. Based on this, a new approach for managing complexity in variant-rich product development was developed. It encourages the reader to manage product development's complexity. In this approach, complexity is systematically analyzed and evaluated to create conditions for a target oriented managing and controlling of complexity in product development.
10419/209191; https://econpapers.repec.org/RePEc:zbw:hiclpr:22
Keywords: 650; Complexity; Complexity Management; Approach; Product Development